A vicious cycle of frailty and acute lower respiratory infection among community-dwelling adults (≥ 60 years): Findings from a multi-site INSPIRE cohort study, India. - Siddhartha Saha; Ritvik Amarchand; Rakesh Kumar; Aslesh O Prabhakaran; Prabu Rajkumar; Sumit Dutt Bhardwaj; Suman Kanungo; Radhika Gharpure; Kathryn E Lafond; Eduardo Azziz-Baumgartner; Anand Krishnan (PLOS Global Public Health)
We studied the relationship of frailty and acute lower respiratory infection (ALRI) among a multi-site cohort of community-dwelling older adults aged ≥60 years in India. During January 2019‒January 2020, participants completed the Edmonton Frail Scale (EFS) at baseline and every 3 months at four sites in India, with each participant completing a maximum of four surveys. Participants were categorized as non-frail (0-5 points), vulnerable (6-7 points), and frail (≥8 points) based on EFS score. Project nurses made weekly home visits to identify ALRI episodes with onset during past 7 days. We estimated adjusted hazard ratios (aHR) for having an ALRI episode within 90 days after EFS by frailty category. We also assessed risk of deterioration of frailty during 7-100 days after ALRI episode onset in terms of an increased EFS score by ≥1 point and change of frailty category. Among 5801 participants (median age 65 years, 41% males), 3568 (61·5%) were non-frail, 1507 (26%) vulnerable, and 726 (12·5%) frail at enrolment. Compared with non-frail participants, the hazard of an ALRI episode was higher among vulnerable (aHR: 1·6, (95%CI 1·3-2.0) and frail participants (aHR: 1·7, 95%CI 1·3-2·2). Participants having ALRI within the past 7-100 days were at increased risk of worsening frailty category (aOR: 1.9, 95%CI 1·3-2.8) compared to participants without an ALRI episode during the same period. The association between ALRIs and worsened frailty suggests prevention of ALRIs through vaccination and other strategies may have broad reaching health benefits for older adults.